Farmer’s pesticide uses and risks in onion fields in the central rift valley of Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2025)
Improper use of pesticides has been the most problematic factor in affecting the environment and pollinating insects. Therefore, this research was conducted to assess farmers’ awareness and usage of insecticides for the protection of onion pests in the Central Rift Valley of Ethiopia from January to May 2022. A purposive sampling method was used to select onion growers in the study area. The respondents revealed that damage caused by pests and diseases led to yield loss in onions, and their choice was applying insecticide chemicals without training in the application technique of the chemical. A very high proportion of farmers (60%) in Adami Tullu Jido Kombolcha and Bishan Guracha (44%) never wear personal protective equipment (PPE) at the time of insecticide application. The result also demonstrated that only 44% of respondents from Adami Tullu Jido Kombolcha and 25% from Bishan Guracha had attended formal training. They also revealed that they purchased pesticide chemicals without knowing their safe use or disposal methods. Due to this, farmers fail to follow the label for pesticide rate, spray volume, and wearing personal protective equipment. The results of this study suggest that farmers in the study area need training and inspection on the safe use and hazardous effects of insecticides.Int. J. Agril. Res. Innov. Tech. 15(1): 11-21, June 2025